The value of Hawaiʻi 2 : ancestral roots, oceanic visions - Yamashiro, Aiko, 1984-; Goodyear-Kaʻōpua, Noelani (Biography monograph., 2014)
How can more of us protect and create waiwai, value, for coming generations? Culturally-rich education. Holistic health systems. Organic farming and aquaculture. Creative and conscious urban development. Caring for one another across difference. Telling our stories. Continuing the conversation of The Value of Hawaiʻi: Knowing the Past, Shaping the Future, this new collection offers passionate and poignant visions for our shared futures in these islands. The fresh voices gathered in this book share their inspiring work and ideas for creating value, addressing a wide range of topics- including community health, agriculture, public education, local business, energy, gender, rural lifestyles, sacred community, activism, storytelling, mo'olelo, migration, voyaging, visual art, music, and the 'aina we continue to love and malama. By exploring connections to those who have come before and those who will follow after, the contributors to this volume recenter Hawaiʻi in our watery Pacific world. Their autobiographical essays will inspire readers to live consciously and lead ourselves as island people-- Back cover.